KEY CHALLENGES IN REFORMING SERBIA’S HEALTH SYSTEM IN THE CONDITIONS OF THE COVID-19 PANDEMIC ON THE WAY TOWARDS A SUSTAINABLE AND DECENTRALIZED SYSTEM - Despotovic, Mile Lj (PONS - medicinski časopis, 2022)
Health care is the most important activity and human kind is dealing with its organization for centuries. Public health policies and functional health care systems have as their primary objectives the preservation and improvement of public health. Problems of intensive aging of the population, continuous growth of health spending, ensuring sustainable financing of health systems and efficient use of resources are present in all world health systems. Health care system reforms have become a global phenomenon for the last twenty years of the last century. The goal of this review paper is to point out the importance and need for timely modifications of the strategy of the health care optimization plan in Serbia by 2035, so that the health care system of Serbia would be ready to respond to potential global health crises in the future. The Plan for optimizing the health care institutions network by 2035 as a key document of the Master Plan will be briefly presented with an analysis of key parameters of health care effectiveness and above all improvement of the implementation of basic principles of health care – uniformity and availability of health services on the territory of Republic of Serbia. In order to present future key changes in the health system, it is necessary to take into account the current situation, as well as the potential consequences of the global pandemic of COVID-19 virus on health systems. Databases were used for analysis: WHO, OECD, World Bank Reports. The tendency of increasing the share of health care costs in GDP, with the problems of efficient use of health care resources, is becoming the most important reason for reforming health insurance and health care in almost all countries in the world. Numerous researches of eminent experts in the field of economy and finance indicate that the introduction of compulsory health insurance with a clearly defined package of health conditions is the most rational choice in the implementation of the World Health Organization project: „Health for all in the 21st century”. A health system could be said to be effective if it provides health care of maximum quality in terms of medical outcome, with minimal costs in relation to the allocated funds. Health care systems around the world today face very similar problems, and the COVID-19 pandemic has shown how „vulnerable” it is not only the health system but all of humanity when faced with such challenges. Keywords: health care, financing, uniformity, accessibility, reforms